Learning Windows PowerShell - Long, Mark (Infinite Skills, 2014)
"In this Learning Windows PowerShell training course, expert author Mark Long will teach you how to use this task-based command-line shell and scripting language, built on the .NET framework, designed especially for systems administration. This course is designed for the absolute beginner, meaning no prior experience with Windows PowerShell is needed."--Resource description page.
Title from resource description page (viewed December 11, 2014)
Keywords: Microsoft Windows (Computer file); Windows PowerShell (Computer program language); Windows PowerShell (Langage de programmation); Electronic videos